Determining an appropriate finite element size for modelling the strength of undrained random soils. (September 2015) - Huang, J.; Griffiths, D.V.
Abstract: The mechanical properties of soils and rocks can be highly variable, and there has recently been a great deal of interest in modelling this variability using random field theory, in which the material properties vary from point to point. When these point-wise material properties are mapped onto a finite element mesh, discretization errors are inevitable. In this study, the discretization errors are studied and suggestions for element sizes in relation with spatial correlation lengths are given.